Improving English Speaking Skill Through Flashcards In The Second Grade of SD Islam Al Huda - Irianto, Siti Nur Aliza (Arden Jaya Publisher, 2025)
This research aims to improve the English speaking skills of the second-grade students at SD Islam Al-Huda by using flashcards as a learning media. The study employed a classroom action research design conducted in one cycle. The instruments used in collecting data were observation checklists, teacher’s logs, field notes, interviews, and speaking assessment rubrics. The findings show that the use of flashcards significantly improved students’ fluency, pronunciation, vocabulary mastery, grammatical accuracy, and confidence in speaking English. The consistent implementation of flashcards not only enhanced students’ vocabulary acquisition but also increased their willingness to communicate actively. Therefore, flashcards are proven to be an effective learning media to support the development of English speaking skills at the elementary school level.